Modeling of the effects of cathode catalyst layer design parameters on performance of polymer electrolyte membrane fuel cell. (1st November 2020) - He, Pu; Mu, Yu-Tong; Park, Jae Wan; Tao, Wen-Quan
Highlights: An improved three-dimensional multiphase non-isothermal PEMFC model is established. The effects of five design parameters of CCL on cell performance are investigated. Low Pt loading is more likely to cause oxygen starvation. Increase of I/C ratio is better for the uniformity of membrane water distribution. Abstract: A comprehensive macroscopic three-dimensional multiphase non-isothermal polymer electrolyte membrane fuel cell (PEMFC) model coupled with an improved electrochemical kinetics model considering the geometric structure parameters of the cathode catalyst layer (CCL) and oxygen transport process in CCL is developed. The effects of five CCL design parameters are investigated. It is found that the Pt loading of CCL has a significant effect on the performance, a low platinum (Pt) loading is more likely to cause oxygen starvation. The increase of Pt/C ratio can promote the performance significantly at a lower Pt/C ratio. A lower I/C ratio is good for the enhancement of limiting current density, a larger I/C ratio is good for the increase of maximum power density, and the increase in I/C ratio is better for the uniformity of membrane water distribution. With the decrease of carbon particle radius, the oxygen concentration on the Pt surface of CCL increases significantly. The increase of electrochemical specific area (ECSA) of Pt particles can promote the performance. In addition, a discussion on applicability of new correlations of capillary pressure-water saturation and effective diffusivity and their effects on the predicted PEMFC performance is presented.